Prevalência de eventos infecciosos em pacientes submetidos a revascularização do miocárdio - (:unkn) unknown (Universidade Federal do Amazonas - Universidade Federal do Pará, 2012)
CABG has as main function to supply the heart muscle blood, and became a great treatment option for arterial disease. But like any surgical procedure, the risk of infection becomes paramount, becoming one of the most frequent complications after these procedures. There are other factors that may be associated with even more with increased infectious risk as: existing Comorbidities intra operatively procedures and/or post-operative complications. Quantitative and transversal study in which we attempted to analyze the prevalence of infection in patients who underwent CAGB between the period from 2008 to 2011, with data collection in medical records of patients admitted to the FHCGV. Statistical analysis was performed on the logistic regression model, and considered a p value of 0.05. In the analytical statistics were used the exact test Chi square test and fisher, such analyses were performed on the Epi-info 3.5.1. 223 charts were analyzed, Staphyloccocus aureus, was the most frequent infectious agent (43.5%). When the variables were analyzed by logistic regression, and are associated with significantly (p < 0.05) with infection: age, smoking, pulmonary complications, pacemaker, hospitalization and ICU. And associated with death are: age, elective, transfusion and not surgery. In relation to the death, the ICU acted as protective factor. The infectious process after the CABG, is a complication exists, and can be explained by various reasons, existing Comorbidities, intraoperative events and/or post-operative complications. This work showed that age, smoking, pulmonary complications, length of ICU hospitalization time and acute renal failure, are associated with increased infection. This age-associated mortality surgical circunstances (urgent/emergency) and in post-operative transfusion.
Keywords: Cirurgia cardíaca; Revascularização do miocárdio - infecção; CIÊNCIAS DA SAÚDE